Torsion of gravid horn of bicornuate uterus: a rare case report - Chundawat, Rama Singh; Rastogi, Radha; Tak, Apoorva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Torsion uterus is a rare complication of the third trimester of pregnancy. Etiological factors associated are myoma, mullerian anomalies, ovarian cyst, sudden change of lie of fetus and trauma. We report a rare case of levorotation of the gravid horn of bicornuate uterus leading to severe abruption and intrauterine death of the fetus. The case was managed by an emergency laparotomy with excision of the atonic gravid horn of bicornuate uterus. This is the third such case reported in the English literature as per our knowledge.